Obtenção e caracterização preliminar de um draft assembly do genoma de cana-de-açúcar (Saccharum spp.) - Souza, Isabela Pavanelli de (2019)
Sugarcane is known as one of the most important crops worldwide, and Brazil is its major producer. Its genome is extremely complex: high chromosome number, highly abundant in repetitive DNA, variable levels of polyploidy, aneuploidy, heterozygosity, and interspecific origin. As a consequence, sugarcane has one of the largest genomes among grasses, comprising about 10 Gb. The first step towards achieving a reference genomic sequence for the crop is to produce a suitable draft assembly. The objective of this study was to build and preliminary characterize a draft genome assembly for the Brazilian sugarcane cultivar RB867515 (Saccharum spp.). Genomic reads were obtained using Illumina and PacBio technologies on genomic DNA extracted from RB867515 lateral buds. After filtering, the assembly was generated using three different approaches, and the best of them was characterized regarding repetitive DNA content, gene prediction, assembly contiguity and completeness. The draft assembly for RB867515 comprised 660,749 scaffolds, with mean size of 1,856 bp, N50 of 9,682 bp, adding up to 1.1 Gb. This size, that represents ~23% of the estimated genome size (1C) for sugarcane (5.32 Gb), is compatible with a monoploid version of the genome. The repetitive DNA content was estimated in 49.7%, with 37.1% of retrotransposons, 9.2% of DNA transposons, 1.5% of satellite DNA and 0.6% of simple repeats. Among retrotransposons, LTR elements were the most abundant (35.2%). A total of 82,945 putative genes were predicted, with mean size of 1,473 bp, ranging from 200 bp to 33 kb. We found that ~19,0% of sorghum chromosomes were represented in the draft assembly. For S. spontaneum chromosomes this rate was 60,1%. This is the first draft genome assembly described for the Brazilian sugarcane cultivar RB867515, the most cultivated in Brazil. We conclude that the draft assembly generated is a useful genomic resource for the culture. Adding a larger set of long reads is going to benefit the assembly, raising its total size, contiguity and completeness.